2020
DOI: 10.1155/2020/1805418
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Fecal Microbiome and Metabolomics in T2DM Rats Reveal Antidiabetes Effects from Host-Microbial Metabolic Axis of EtOAc Extract from Sophora flavescens

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease. Sophora flavescens (S. flavescens), also named Kushen, is a famous Chinese herbal medicine that has been used to prevent and cure T2DM both in folk medicine and in medical institution. However, its mechanism of action remains unclear. In this study, the pharmacodynamic effects of S. flavescens EtOAc extract (SFE) on high-fat diet and low-dose streptozotocin-induced T2DM rats were examined. Fecal metabolomics analysis and 16S rRNA gene sequencing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…On the contrary, Schwiertz et al (2010) reported a significant increase of Bacteroidetes in obese and overweight subjects. Shao, Liu, Wang, Luo, and Chen (2020) reported that Bacteroidetes and Proteobacteria were increased in high fat diet–STZ‐induced T2DM rats, while Firmicutes was decreased. Zhao et al (2019) reported the similar changes in T2DM rats.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Schwiertz et al (2010) reported a significant increase of Bacteroidetes in obese and overweight subjects. Shao, Liu, Wang, Luo, and Chen (2020) reported that Bacteroidetes and Proteobacteria were increased in high fat diet–STZ‐induced T2DM rats, while Firmicutes was decreased. Zhao et al (2019) reported the similar changes in T2DM rats.…”
Section: Discussionmentioning
confidence: 99%
“…DM, as a common metabolic disease, causes numerous organ and system dysfunctions, including the male reproductive system [ 24 ]. Gut microbiota are believed to be vital in regulating DM [ 25 ]. They also affect other systems, such as the nervous system and reproductive system [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, the relationship between DM and gut microbiome has attracted more and more attention. The pharmacodynamic effects of Sophora flavescens EtOAc extract on high-fat diet and low-dose streptozotocin-induced T2DM rats were examined, and the results showed that the Sophora flavescens EtOAc extract may have an effect on T2DM by mediating the host-microbial metabolic axis [ 3 ]. Several reported microbial metabolites related to the gut microbiota were associated with an increased risk of incident type 2 diabetes, reducing insulin secretion and insulin sensitivity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%